2008 Proceedings IEEE INFOCOM - The 27th Conference on Computer Communications 2008
DOI: 10.1109/infocom.2007.157
|View full text |Cite
|
Sign up to set email alerts
|

Inside the New Coolstreaming: Principles, Measurements and Performance Implications

et al.

Abstract: Abstract-The Peer-to-Peer (P2P) based video streaming has emerged as a promising solution for Internet video distribution. Leveraging the resource available at end users, this approach poses great potential to scale in the Internet. We have now seen the commercial P2P streaming systems that are orders of magnitude larger than the earlier academic systems. We believe understanding its basic principles and limitations are important in the design of future systems.The Coolstreaming, first released in summer 2004,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
189
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(194 citation statements)
references
References 9 publications
3
189
0
2
Order By: Relevance
“…A Block Map (BM) is introduced to specify the availability of blocks at each peer [64]. The periodic exchange of BMs among peers enables them to locate the required blocks.…”
Section: Fs2youmentioning
confidence: 99%
“…A Block Map (BM) is introduced to specify the availability of blocks at each peer [64]. The periodic exchange of BMs among peers enables them to locate the required blocks.…”
Section: Fs2youmentioning
confidence: 99%
“…BAR Gossip [20] and Flightpath [19] focus on tolerating the presence of byzantine peers. In Coolstreaming [18], the content location is pushed while the actual content is pulled as in swarming systems. HEAP [9] accounts for peers heterogeneity by letting nodes dynamically adjust their contribution to gossip dissemination according to their capabilities.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, gossip-based approaches have been extensively used in the context of streaming applications [18,20,34]. Some recent work [3] has demonstrated that epidemic live streaming algorithms can achieve nearly unbeatable rates and delays.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in [22], different implementations lead to different start-up delays. Generally, efficient distribution process enables the peers grab chunks quickly when they first join the system.…”
Section: Comparison Of Start-up Delaysmentioning
confidence: 99%